2004
DOI: 10.1111/j.1365-4632.2004.02152.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous larva migrans (creeping eruption) in an urban slum in Brazil

Abstract: This population-based study showed that CLM is endemic in this deprived community. The number of lesions and their topographic localization are in contrast with those obtained in previous reports based on the examination of individuals or groups affected in small outbreaks. We conclude that the clinico-epidemiologic pattern of CLM in a deprived community is different from that observed in travelers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 33 publications
2
30
2
Order By: Relevance
“…Cutaneous larva migrans occurs mainly in tropical areas and has also been reported from temperate climatic regions (Heukelbach and Hengge 2009). The condition is endemic in humans in deprived communities (Heukelbach et al 2004). The high prevalence of hookworms in stray dogs in the present study indicates that this condition could be more widely distributed than it is currently assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous larva migrans occurs mainly in tropical areas and has also been reported from temperate climatic regions (Heukelbach and Hengge 2009). The condition is endemic in humans in deprived communities (Heukelbach et al 2004). The high prevalence of hookworms in stray dogs in the present study indicates that this condition could be more widely distributed than it is currently assumed.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Manaus, Brazil, showed an astounding prevalence of 9.4% in children during the rainy season (A. Schuster, H. Feldmeier, unpublished observation 2009). In urban slums and impoverished rural communities in Northeast Brazil, up to 4% of the general population and 15% of children have been found to be infested [10][11][12]. As a rule, a high incidence of HrCLM in the human population reflects the presence of many (stray) dogs and cats which are infected with hookworms, which are not, or not regularly, treated with anthelmintics [17].…”
Section: Disease Occurrencementioning
confidence: 99%
“…HrCLM is endemic in many resource-poor communities in the developing world [9][10][11][12][13][14][15][16]. A study in Manaus, Brazil, showed an astounding prevalence of 9.4% in children during the rainy season (A. Schuster, H. Feldmeier, unpublished observation 2009).…”
Section: Disease Occurrencementioning
confidence: 99%
“…Crime, alcoholism, adolescent prostitution, and domestic violence are major social problems, and most inhabitants are desperately poor. The prevalence of parasitic skin diseases such as pediculosis, scabies, tungiasis, and cutaneous larva migrans is high (Heukelbach et al 2004(Heukelbach et al , 2005a.…”
Section: Settingmentioning
confidence: 99%